P250 Review of referrals to sleep clinics in glasgow. (14th November 2013) - Livingston, C; Rouse, M; O'Dowd, C; Carlin, C; Grieve, D; Livingston, E
Abstract : Aim: There is increasing pressure within Sleep Services in NHS GGC. To manage the service appropriately we felt that robust and evidence based referral guidance should be available for potential referrers. We sought to develop these by analysing content of current referrals to the service, to establish whether there was any link with clinic outcome. Method: Referrals to sleep services were audited throughout NHSGGC for the month of November 2012. We looked for information that would be helpful in pointing toward a diagnosis of OSAS. This was; the presence of snoring, witnessed apnoeas, daytime somnolence, Epworth sleepiness score (ESS) and BMI. We also looked at the outcome of the consultation in terms of whether or not further investigation was required and whether or not the patient was discharged after the first clinic appointment. Results: There were 156 referrals received. 66% were from GPs. Referral from other respiratory departments constituted 17% of referrals, from ENT departments 8%, with 9% of referrals coming from various other medical specialties. The presence of snoring was recorded in 60% of all referrals, witnessed apnoeas in 58%, daytime sleepiness in 67%, ESS in 30% and BMI in 31%. Only 55% of all referrals included 3 or more of the above pieces of information. Occupation/driving status was recorded in only 17% of all referrals. 63% of all patients went on to have a sleep study performed, with 36% being discharged after the first clinic appointment. There appeared to be a relationship between what was recorded in the referral letter and 'clinic outcome.' When 3 or more of snoring, witnessed apnoeas, daytime sleepiness, ESS and BMI had been recorded in the referral letter, only 19% of patients were discharged after the first clinic visit without further investigation. This figure rose to 39% when less than 3 of the above items were recorded. This trend appeared more marked specifically looking at GP referrals (20% vs 46%). Conclusions: This analysis of referrals would suggest that the quality of referral letters is linked to clinic outcome. Referrals containing very little information resulted in more patients being discharged directly from the clinic without investigation. Referral guidelines for general practice will hopefully improve the quality of referrals.